THE EFFECTIVENESS OF EDUCATION TYPE AND METHOD ON IMPROVING THE ORTHOPEDIC SURGICAL PATIENTS' KNOWLEDGE AND CAPABILITY: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i1.61 - Eni Purwanty (International Journal of Nursing and Health Services (IJNHS), 2019)
Introduction: The success orthopedic surgery patients’ education depends on many factors, including the accuracy in choosing methods and the educational media used. This selection is based on consideration of the appropriateness of the material provided for the patient's needs and the learning objectives to achieve. The purpose of this literature review is to identify the types of methods and educational media employed to improve self-knowledge and abilities of orthopedic surgery patients. Method: The references employed in this literature review were four experimental research articles published in 2010 to2018. The keywords appropriateness in the search were "orthopedic patient", "patient education", "patient knowledge", "education method", and "patient outcome "through the ProQuest database, EBSCO, Sage, and Clinical Key. Results: This review shows that the media and educational methods vary widely, including face-to-face education, web-based or internet-based education, education with DVD videos, and structured education. Statistical analysis shows that all of these methods can improve the knowledge and skills of orthopedic surgery patients in undergoing the perioperative phase. Conclusion: Using structured educational methods with media combined with web-based or internet education and DVD video education with direct education (face to face) is considered good for education established for patients. Meanwhile, using education with DVD videos is considered good skill enhancement education.